2020
DOI: 10.15386/mpr-1312
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stress induced in mandible around an implant-supported overdenture with locator attachment and telescopic crowns – a finite element analysis

Abstract: Introduction. One of the principle factors for the success of implant supported/retained overdentures (IOs) is the manner in which the stresses are transferred to the surrounding bone. Hence, the aim of the present study is to compare the stress induced in the mandible around IOs, using two different attachment systems, locator and telescopic. Methods. 3D finite element models were prepared using Pro/ENGINEER or PTC Creo to simulate 4 clinical situations: IOs using two different attachment systems, locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Similarly, because of the cantilever effect of splinted bar, the deflection was of greater value causing high stresses at the level of the contact zone of the abutment, implant and screw. 53 In the present trial the ball and locator attachment are considered as unsplinted attachment, while for the telescope attachment it exerted a secondary splinting effect. Results of the present study showed that the ball attachment has recorded the greatest bone height changes when compared to the locator and telescope attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, because of the cantilever effect of splinted bar, the deflection was of greater value causing high stresses at the level of the contact zone of the abutment, implant and screw. 53 In the present trial the ball and locator attachment are considered as unsplinted attachment, while for the telescope attachment it exerted a secondary splinting effect. Results of the present study showed that the ball attachment has recorded the greatest bone height changes when compared to the locator and telescope attachment.…”
Section: Discussionmentioning
confidence: 99%
“…41 This agreed with many studies. 1,41,42 Ball attachments transferred less stress to the canines and the cortical alveolar bone of the canines than resilient telescopic crowns, but transferred more stress to the cortical bone of alveolar process at the distal end of the overdenture. Ball attachment allows free movement in several directions while resilient telescopic crowns allow free vertical movement.…”
Section: Discussionmentioning
confidence: 99%
“…6 Telescopic overdenture is a prosthesis that includes a primary crown cemented to the abutment and a secondary crown attached to the prosthesis and fits on the primary crown. 1,7 Three types of telescopic crowns have been described: the parallel-walled crowns, the conical crowns with tapered design, and the resilient crowns with clearance fit. 3,8 Clearance fit means free space between primary and secondary crowns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that, although four mini-implants have been recommended as an alternative treatment for the edentulous patients, no published evidence indicated that this option is better than the use of two. The telescopic copings for group II were fabricated according to the resilient design, to allow a slight movement of the overdenture to avoid stresses on the implants (19) .…”
Section: Discussion Of the Methodologymentioning
confidence: 99%